Kajian Teori Behavioral Approach Of Leadership: Studi Literatur Review - Wahdatul Laili; Musayaroh Musayaroh; Moh. Ishaq; Mochammad Isa Anshori (International Forum of Researchers and Lecturers, 2023)
Leadership is the ability to influence the behavior of a group towards achieving goals. The main focus of this research is the behavioral approach of leadership in the context of management. This approach emphasizes the behavior and actions of leaders as the main factors in influencing individual and group performance in organizations. The purpose of this study is to analyze various theories and research related to the behavioral leadership approach, the concept of leadership behavior approach, leadership style based on the behavioral approach, various behavioral approach theories, such as the Michigan study, the Ohio study, and the Managerial Grid/Leadership grid, as well as various case studies from previous studies. The method used is a literature review study method, such as from books, journals, and several previous studies. The results of this study emphasize the importance of an effective leadership behavior approach in achieving organizational goals. Leader behavior has a significant influence on employee motivation, performance, and satisfaction. Therefore, it is important for organizations to understand and implement effective leadership principles and styles to create a productive and motivating work environment.